Notes on Indigenous People from the South of the Province of Dalmatia (Examples from East Herzegovina) - Samardžić, Gligor M. (Collection of Papers of the Faculty of Philosophy in Priština, 2024)
The paper presents data on indigenous people from the area of east Herzegovina (the south of the province of Dalmatia). After the defeat of the Illyrians and the establishment of educational goals in the Roman province of Dalmatia, territorial and ethnic changes occurred with certain tribes that academic circles were poorly informed about. The indigenous feature, as indicated by the Illyrian names on the epigraph statues of east Herzegovina, is significant. By conquering the Illyrian territory and establishing power over it, the Romans left its inhabitants certain autonomy, followed by the processes of urbanization and Romanization from the 1st to the 4th century. After occupying the Illyrians, the period in which the indigenous people were introduced into Roman social and political order commenced. The following period was marked by the penetration and establishment of the ancient culture and civilization in the Balkans as well as by the work on the rule managemant with the Illyrians. Epigraph statues, various archeological findings and oral sources shed light to a certain extent on these processes in the territory of east Herzegovina. Archeological research and epigraph materials point to the conclusion that the areas in the inland of east Herzegovina (the south of Dalmatia) in the Roman period managed to perservere their regional ethnic characteristics for an extended period of time, which is best seen in the onomastics from Dobrićevo, Ljubomir, Fatnica, and Nevesinje. Some of the characteristic names found on epigraph statues from this area are Zorada, Zanatis, Tattaris, Temus etc. Regional onomastics testifies that the traditional lifestyles perservered in the Roman period for an extended period of time. However, inscriptions can still be found with indigenous Illyrian names that were to some extent adapted to the Roman onomastic system.